Pengaruh School Readiness dan Parent Involvement Terhadap Prestasi Belajar Siswa SD Kelas I XYZ di Bandung - Sesilia Pradwitasari (Magister Teknologi Pendidikan Fakultas Pascasarjana Pendidikan Universitas Pelita Harapan, 2024)
First grade is the first formal education for every student. The transition into first grade is important because it sets the foundation for future academic achievement. A ready student with parents support will make the transition works well and it will effect positively on their academic achievement. This study measures school readiness which includes physical development, language development, cognitive development, social emotional development and approach of learning. Parent involvement is the commitment of parent throughout themselves and their role as parent in supporting their child development. Parent involvement data was taken by questionnaire. Quantitative method were used in the study. The method of analysis used is PLS SEM. The result of the study showed school readiness effect positively 36% to academic achievement. The dimension of school readiness that has significant relationship are language development with significant level of 0.000, physical development with significant level of 0.005, social emotional development with significant level of 0.013 and approach of learning with significant level of 0.005. Parent involvement does not effect partially to academic achievement.